Viscoelastic effects on the oscillatory flow in a fluid-saturated porous layer - Raghunatha, K. R.; İnç, Mustafa; Vinod, Y. (Wiley, 2024)
The oscillating flow of the viscoelastic fluid-saturated porous layer has been useful in many areas, including the petroleum, chemical, and bioengineering industries. It is studied using the modified Darcy-Oldroyd-B model in this article. The exact solution is obtained utilizing a simpler and more reasonable method. According to this velocity solution, the time-velocity profile of one kind of viscoelastic fluid is analyzed. From the analysis, it was found that the flow behaves like the Newton fluid when the oscillating frequency is low, and the flow reversal occurs when the oscillating frequency is high. Further, velocity, temperature, shear stress, and the rate of heat transfer are exponential solutions that are obtained and analyzed for different values of known physical parameters. Finally, we recognize that the relaxation and retardation parameters in this model act in the opposite manner.
Keywords: oscillatory flow; porous media; viscoelastic fluid